2021
DOI: 10.21203/rs.3.rs-396201/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the stability of Pd-exchanged sites in zeolites with the aid of a high throughput quantum chemistry workflow

Abstract: Cation exchanged-zeolites are functional materials with a wide range of applications from catalysis to sorbents. They present a challenge for computational studies using density functional theory due to the numerous possible active sites. From Al configuration, to placement of extra framework cation(s), to potentially different oxidation states of the cation, accounting for all these possibilities is not trivial. To make the number of calculations more tractable, most studies focus on a few active sites. We at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…9 to be present at Al pairs in the 6-rings and 8-rings. Additionally, we have considered Pd + and Pd 2+ sites that may be present due to NNN Al pairs in the 4-rings and NNNN Al pairs spanning two or more adjacent rings, identified in a high-throughput study on the stability of Pd cation sites in zeolites by Aljama et al [52]. In these structures, the charge-compensating Pd cations are also located in a nearby 6-or 8-ring, such that they are accessible to adsorbates in the cha cage.…”
Section: No Adsorption In Pd/h-chamentioning
confidence: 99%
“…9 to be present at Al pairs in the 6-rings and 8-rings. Additionally, we have considered Pd + and Pd 2+ sites that may be present due to NNN Al pairs in the 4-rings and NNNN Al pairs spanning two or more adjacent rings, identified in a high-throughput study on the stability of Pd cation sites in zeolites by Aljama et al [52]. In these structures, the charge-compensating Pd cations are also located in a nearby 6-or 8-ring, such that they are accessible to adsorbates in the cha cage.…”
Section: No Adsorption In Pd/h-chamentioning
confidence: 99%
“…Previous studies have shown that Pd 2+ cations charge-compensating two Al tetrahedral sites (2Al) in the six-membered ring (6-MR) are the most thermodynamically stable ion-exchanged Pd 2+ species in CHA, represented here by Z 2 Pd where “ Z ” denotes the substitution of framework Si with Al (Figure ). ,, The lowest-energy Z 2 Pd structure has 2Al in a third-nearest-neighbor (3NN) arrangement (0 kJ mol –1 ), followed by the 2NN configuration (+65–80 kJ mol –1 ). ,,, One Al T-site (1Al) can be charge-compensated by Pd + cations (ZPd) or by Pd 2+ as [PdOH] + (ZPdOH). The ZPd structure is +28–60 kJ mol –1 higher in energy than 3NN Z 2 Pd. , The existence of Pd + after high-temperature treatments in air with and without H 2 O is debated in the literature; direct characterization of Pd + has been reported only from EPR measurements of Pd/Y zeolites performed under vacuum and after H 2 treatment at 298 K .…”
Section: Resultsmentioning
confidence: 99%
“…The ZPd structure is +28–60 kJ mol –1 higher in energy than 3NN Z 2 Pd. , The existence of Pd + after high-temperature treatments in air with and without H 2 O is debated in the literature; direct characterization of Pd + has been reported only from EPR measurements of Pd/Y zeolites performed under vacuum and after H 2 treatment at 298 K . ZPdOH has been identified in detectable amounts only for CHA materials containing a larger number of ion-exchanged Pd 2+ species than 2Al sites in the 6-MR and is computed to be +60–79 kJ mol –1 higher in energy than 3NN Z 2 Pd. ,, The Pd content of the Pd-CHA-X-ND samples here (Pd/Al = 0.05–0.08) is much lower than the number of available 2Al 6-MR sites quantified by Co 2+ titration (Co 2+ /Al = 0.12). Thus, we expect Pd 2+ in the 6 MR 3NN configuration to be the predominant cationic species in our materials; however, for comparison, we also considered 2NN Z 2 Pd, ZPd, and ZPdOH in the analyses below.…”
Section: Resultsmentioning
confidence: 99%
“…(12) Characterization of zeolite-encapsulated sub-nanometre clusters is experimentally challenging, owing to the size resolution limitations of most imaging methods, the sensitivity of zeolites to beam damage in electron microscopes and the lack of sensitivity of spectroscopic methods towards the low loadings of metal (often < 0.1 wt %). (13)(14)(15) High resolution TEM imaging remains a preferred method for characterising metal atoms and clusters, [2,7] and has been successfully employed for detecting and determining cluster size, coordination environment and oxidation state, in cooperation with EXAFS and XPS. [8] Nevertheless, ex situ characterization of as-prepared or spent https://doi.org/10.26434/chemrxiv-2023-9g3fn ORCID: https://orcid.org/0000-0001-8034-6121 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%